Fear of COVID-19 among critical care nurses of public hospitals in Lahore: empirical evidence during third wave - Asma Nadeem; Rubina Jabeen; Shehla Nazir; Shahbaz Haider (PAGEPress Publications, 2023)
The world has seen a pandemic which disrupted the life. Till now there are aftershocks of the COVID-19 such as Omicron instilling fear among individuals. Healthcare staff is on alert specifically the nurses has suffered a lot mentally due to this issue by developing fatigue. The study conducted during deadly 3rd COVID-19 wave. The data were collected by developing the questionnaire of the previously validated measures related to the variables under study from nurses working in the intensive care unit, critical care unit and floor wards of COVID-19 at Services Hospital, Lahore. A total of 140 questionnaires were used for data analysis. The study used Statistical Package for Social Sciences for frequency and descriptive statistics. Whereas, the outcomes of fear of COVID-19 were assessed by using the latest Smart Partial Least Squares software which allows to assess the complex research frameworks. The results of the study revealed that the fear of COVID-19 results in poor quality of life among nurses and fatigue. Resilience among nurses can reduce the negative consequences but did not get the statistical support.